Evaluation of the Bioefficacy of a Stabilized Form of Human Growth Hormone (SP-hGH) - Lee, S.-B.; Park, H.; Koh, J.; Lee, H.; Kim, J. (Hormone and Metabolic Research, 2013)
Protein aggregation is a major obstacle in maintaining the stability of therapeutic proteins. In previous studies, fusion between a stabilizing peptide (SP) and human growth hormone (hGH) resulted in improved solubility and stability compared with hGH alone, although the bioactivity of the protein was not confirmed in vivo. In this study, we evaluated the bioefficacy of hGH and SP-hGH in vivo using a mouse model. Subcutaneous injections of 30 μg of hGH or SP-hGH were administered to 8-month-old female mice, twice a week for 14 weeks. Neither hGH nor SP-hGH significantly affected body weight or blood glucose levels compared with control mice. Interestingly, abdominal fat was significantly reduced in SP-hGH-treated mice compared with hGH-treated mice. While total cholesterol, HDL, and LDL levels were slightly higher in both groups, TG levels were significantly reduced in both SP-hGH and hGH-treated mice compared with control mice. IGF-1 levels in the liver were increased in both the SP-hGH and hGH groups, thereby inducing liver cell proliferation. These results suggest that SP fusion with hGH attained similar or improved bioefficacy compared with hGH alone.
Keywords: protein aggregation; protein stability; stabilizing peptide; human growth hormone